P151 RIGHT VENTRICULAR MECHANICS IN PATIENTS AFFECTED BY PULMONARY VALVE STENOSIS, BEFORE AND AFTER PERCUTANEOUS PULMONARY VALVULOPLASTY. (18th May 2022) - Sirico, D; Spigariol, G; Mahmoud, H. T; Basso, A; Reffo, E; Biffanti, R; Sabatino, J; Di Candia, A; Castaldi, B; Di Salvo, G
Abstract: Aim of the Study: To evaluate the mechanical changes of the right ventricle in patients undergoing balloon pulmonary valvuloplasty using transthstandard transthoracic echocardiography (TTE) and speckle–tracking echocardiography (STE) and to investigate the correlation between haemodynamic and echocardiographic parameters before and after treatment. Materials and Methods: 43 pediatric patients (19 males), mean age 3, 2±4, 9 years with severe pulmonary valve stenosis and indication for percutaneous balloon valvuloplasty were recruited. All patients underwent TTE and STE with analysis of right ventricle global longitudinal strain (RVGLS) one day before and after the procedure. For each patient were collected invasive parameters during balloon valvulopasty. Results: After the procedure, there was an immediate reduction of both peak–to–peak transpulmonary gradient (Dp post) and ratio between the systolic pressure of right and left ventricle (RV/LV ratio) with a drop of 29, 3±14, 67mmHg and 0, 43±0, 03, respectively. Post–procedural echocardiography showed peak and mean transvalvar pressure gradient drop (50±32, 23 and 31±17, 97, respectively). The degree of pulmonary valve regurgitation was mild in 8% of patients before the procedure, following the intervention it reached 29% with a statistically significant increase (p = 0, 007). However, moderate and severe regurgitation remained stable after the procedure. There was a significant improvement of Fractional Area Change (FAC) after the procedure (40, 11% vs 44, 42%, p = 0, 01). TAPSE (p = 0, 60) and longitudinal strain (p = 0, 31), did not improve significantly after intervention. Finally, pre–procedural invasive RV/LV ratio showed good correlation to echocardiographic transvalvular peak and mean pressure gradient (R = 0, 375, p = 0, 019 and R = 0, 40, p = 0, 012, respectively), as well as with FAC (R = 0, 31 p = 0, 05), TAPSE (R = 0, 62 p < 0, 001)and RVGLS (R = 0, 46 p = 0, 01) Conclusions: Percutaneous balloon pulmonary valvuloplasty represents an efficient and safe procedure. Right ventricular global systolic function improved following afterload reduction, while longitudinal systolic function did not show improvement immediately after intervention. Finally, invasive preprocedural RV/LV ratio demonstrated better correlation with echocardiographic evaluation of stenosis degree and right ventricular function compared to invasive peak–to–peak pressure gradient. Therefore, RV/LV ratio should be preferred for the assessment of pulmonary valve stenosis.